Refleksja epistemologiczna jako narzędzie budowania własnego potencjału edukacyjnego przyszłych nauczycieli - Zdybel, Dorota (Nauczyciel wczesnej edukacji: Rozwijanie kompetencji zawodowych, 2016)
Educational system of teachers training in Poland is focused on developing professional competencies, mainly didactic competencies directly involved in the process of teaching particular school subjects. The absent element is metacognitive awareness defined as an ability to critically reflect on the course and effectiveness of one’s own thinking – awareness which stands at the core of teachers professional development. The aim of this article is to present the essence and dimensions of epistemological reflection, to explain its influence on teachers’ personal theories and hidden presumptions concerning knowledge and learning. Another am is to present the role of teachers’ personal epistemology in building classroom culture of learning. Theoretical considerations will be illustrated with examples of students’ drawings and statements, collected during pilot study on future teachers’ conceptions of mid.